Anti-interferon-γ autoantibody-associated immunodeficiency. (October 2021) - Shih, Han-Po; Ding, Jing-Ya; Yeh, Chun-Fu; Chi, Chih-Yu; Ku, Cheng-Lung
Abstract : Anticytokine autoantibodies are an emerging disease etiology, through the disturbance of physiological functions of cognate cytokines. Anti-interferon (IFN)-γ autoantibodies (AIGAs) were first identified in patients with severe mycobacterial infections, and were considered to be an autoimmune phenocopy of inborn genetic errors of the IL-12/IFN-γ axis. More than 600 reported cases, most originating from Southeast Asia, have been diagnosed over the last decade. Specific HLA class II molecules are associated with these autoantibodies, which provide a genetic basis for the high prevalence of this immunodeficiency syndrome in certain ethnic groups. Salmonellosis and herpes zoster reactivation are observed in more than half the patients with AIGAs. Moreover, AIGAs have been shown to underlie severe Taralomyce marneffei infection in HIV-negative patients. AIGAs may, thus, be considered a new form of late-onset immunodeficiency conferring a predisposition not only to severe mycobacterial, but also to some bacterial and fungal infections.